Memory Constraints on Hypothesis Generation and Decision Making. (August 2014) - Thomas, Rick; Dougherty, Michael R.; Buttaccio, Daniel R.
Hypothesis generation is the process people use to generate explanations for patterns of data, which is an act vital to everyday problem solving. It is the basis for decision making in many professions, such as medicine, intelligence and reconnaissance analysis, auditing, and fault detection in nuclear power plants. Even laypeople's impressions of acquaintances' personalities based on behavioral patterns can be considered a case of hypothesis generation. This article provides an overview of research elucidating the cognitive processes that underlie hypothesis generation and decision making.